The Influence of Digital Marketing Strategy on Increasing Sales Volume in the New Normal Era: A Case Study at CitraLand Ambon, Indonesia - Reken, Feky (HM Publisher, 2024)
It is no secret that this coronavirus has paralyzed people’s economies in various sectors, especially in the property sector. But slowly now, we are entering an era called the new normal era. Digital marketing is currently an effective strategy that can be utilized by business people, especially property business people, to stay connected with customers online without having to meet face to face. Business people can take advantage of digital media platforms, both web-based and social media. This research aims to: (1) test and analyze the influence of digital marketing via websites on increasing sales in the new normal era at CitraLand Ambon. (2) testing and analyzing the influence of digital marketing via social media on increasing sales in the new normal era at CitraLand Ambon. The sample used in this research was 40 respondents, and these respondents were CitraLand Ambon customers who purchased units online either through social media or websites. The data was tested using multiple linear regression analysis through the SPSS analysis tool. Research results show that: (1) digital marketing via websites has a positive and significant effect on increasing sales at CitraLand Ambon. (2) digital marketing via social media has a positive but not significant effect on increasing sales at CitraLand Ambon.